Pre-workout multi-ingredients or carbohydrate alone promote similar resistance training outcomes in middle-aged adults: a double-blind, randomized controlled trial - Joel Puente-Fernández; Eneko Larumbe-Zabala; Justin Roberts; Fernando Naclerio (Journal of the International Society of Sports Nutrition)
Background Pre-workout multi-ingredients are designed to enhance energy levels and acutely increase exercise performance. This study compared the effectiveness of ingesting an admixture providing caffeinated ingredients and plant-based protein enriched with amino acids versus carbohydrates alone on body composition, hypertrophy and physical performance.Methods Forty-three middle-aged physically active individuals (26 peri- and post-menopausal females and 17 males) completed the study after being randomly assigned to one of the following intervention groups: pre-workout (PREW n = 24, 54 ± 4 years, body mass 77.6 ± 16.0 kg) or a carbohydrate-only comparator (COMP n = 19, 52 ± 4 years, body mass 80.6 ± 16.0 kg). Measurement of fat and fat-free mass (via plethysmography), waist and hip circumferences, muscle thickness (via ultrasound), strength, power output and muscle endurance performance were collected before and after a 6-week resistance training programme performed 3 times per week. Treatment consisted of ingesting 30g of the assigned supplement, mixed with 400mL of plain water, 15min before each workout session.Results Both groups significantly (p < 0.05) reduced fat mass (mean ± SD) (PREW −1.4 ± 1.6 kg; COMP −1.0 ± 1.5 kg), increased fat-free mass (PREW +0.9 ± 1.1 kg; COMP + 0.8 ± 0.9 kg); vastus lateralis (PREW +0.2 ± 0.2 cm; COMP + 0.1 ± 0.6 cm), and elbow flexors (PREW +0.5 ± 0.3 cm; COMP + 0.4 ± 0.2 cm) muscle thickness. Only the PREW group showed a significant reduction in the waist circumference (−1.8 ± 1.8 cm, p < 0.01). However, no significant differences between groups (PREW vs. COMP) were identified at post-intervention. Isometric force, countermovement jump, medicine ball throw, and upper and lower body muscle endurance performance improved (p < 0.05) for both treatments, with no difference between groups.Conclusion Except for waist circumference reduction, ingesting a pre-workout vegan protein-based caffeinated supplement promotes no further resistance training benefits in middle-aged individuals.